The mediating role of organizational capabilities between organizational performance and its determinants - Shafique-ur Rehman; Rapiah Mohamed; Hazeline Ayoup (Journal of Global Entrepreneurship Research, 2019)
The objective of the current research is to determine the influence of management control system (MCS) as a package on organization performance, and organizational capabilities play an important role to explain this relationship. Data were collected from general managers and chief financial officers from the textile industry of Pakistan to empirically test hypotheses of this study. One hundred sixty questionnaires were used in the analysis through partial least square equation modeling technique. The findings elucidated a significant influence of cybernetic, rewards and compensation, and administrative controls on organizational performance. The same findings were found with cultural, cybernetic, rewards and compensation, planning, and administrative controls with organizational capabilities. Despite this, planning controls and cultural controls have no influence on organizational performance. Organizational capabilities mediate the relationship between all five elements of MCS as a package and organizational performance. The findings provide insights to top management of the textile industry to enhance organizational performance by focusing on indicators mentioned in the study. In addition, improvements in organizational capabilities will also enhance organizational performance. The current research is the pioneer study that tests the mediating role of organizational capabilities between MCS as a package and organizational performance with the help of resource orchestration theory and resource-based view theory. Subjects: management accounting, business, performance management.
Keywords: 650; MCS as a package; Organizational capabilities; Organizational performance; Resource orchestration theory; Resource-based view theory